Therapeutic Applications of Phytochemicals for Treatment of Diabetes Mellitus and Future Scope: An Overview - Pavani, Kaza; Naik, Mude Jagadish (Pharmacognosy Reviews)
Diabetes mellitus is a multifaceted metabolic syndrome that is typified by hyperglycemia of long duration due to the inadequate production or action of insulin. Due to the high expenses of synthetic drugs, coupled with their unwanted effects, increasing interest has been generated to turn to phytochemicals bioactive principles obtained from plants to treat diabetes. Recent research has highlighted the therapeutic potential of several phytochemicals, including alkaloids, glycosides, polysaccharides, terpenoids, polyphenols and flavonoids, for their anti-hyperglycemic, anti-hyper lipidemic, anti-inflammatory, antioxidant, and insulinotropic activity. Further studies need to focus on unmasking the molecular mechanisms of these compounds, performing large-scale clinical trials, improving bioavailability, and opening up the prospects of combination therapy. This article presents an extensive review of the complex features of diabetes mellitus pathobiology and the multimodal therapeutic actions of phytochemicals in discussing the present status and future outlook of these interventions.
Keywords: Diabetes Mellitus; Phytochemicals; Antidiabetic; Phytomedicines